Bio-efficacy of halosulfuron methyl against Cyperus spp. in maize (Zea mays L.) - Kumar, Anil; Sharma, Neetu; Sharma, Ashu; Mahajan, Amit; Stanzen, Lobzang (Annals of Agricultural Research, 2016)
A field experiment was conducted at research farm, Division of Agronomy SKUAST-Jammu toevaluate the efficacy of halosulfuron-methyl for the control of Cyperus and other weed species inmaize. The treatments comprised of two different doses of halosulfuron-methyl post-emergence@ 52.5 & 67.5 g/ha, 2,4-D ethyl ester post-emergence @ 900 ml/ha, atrazine pre-emergence @ 500g/ha, two hand weeding at 20 and 35 DAS and untreated control. The results revealed that thelowest density and dry weight of Cyperus spp. as well as higher weed control efficiency and grainyield of the maize crop were recorded with post-emergence application of halosulfuron-methyl @67.5 g/ha which was closely followed by 2, 4-D ethyl ester @ 900 ml/ha The herbicide dosesevaluated in this study did not show any phytotoxicity and residual effect on succeeding wheatcrop.